Identification Damage of PMT 500KV BAY 7A1 Using the Breaker Analyzer and Contact Resistance Methods at the Substation - Helmi Dwi Prasetya; Ulinnuha Latifa; Rahmat Hidayat (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2021)
One of the state-owned companies in the electricity sectors, located in South Bandung with the main function of managing distribution installation assets (Transmission and Substation) and maintenance of distribution installation assets to maintain the continuity of efficient and reliable distribution of high voltage electrical energy. In substations, PMT is the most important component, coordination between PMT divisions must be paid more attention. One of the disturbances in PMT is the high value of contact resistance and it is not synchronous during the Open-Close process. The research was aimed to identify how much the value of contact resistance at each PMT, and how much loss of conductivity of PMT and also carried out simultaneous testing to observe the level of synchronization between phases. After various tests were carried out, by looking at the results of these tests, it could be concluded that the PMT 7A1 had no damage, and could still operate normally. Then, the purpose of maintaining high voltage electrical equipment is to ensure the continuity of electricity distribution and ensure reliability, and to extend the life of the equipment by reducing equipment damage.